157k views
4 votes
What's 5x + 3 = 6x - 2

2 Answers

2 votes

Answer: x=5 and 5=x. *The answer must be have positive sign.*

Explanation:

subtraction property of equality is subtracting the same number from both sides of an equation does not change the equation.

a-c=b-c

first, subtract by 3 both sides of an equation.

5x+3-3=6x-2-3

then, simplify by equation.

5x=6x-5

next, subtract by 6x both sides of an equation.

5x-6x=6x-5-6x

simplify by equation.

-x=-5

divide by -1 both sides of an equation.

-x/-1=-5/-1

finally, simplify by equation.

5/1=5

5*1=5

1*5=5

It change negative to positive sign.

x=5

Hope this helps!

Thanks!

Have a great day!

User Anzil KhaN
by
5.8k points
2 votes

Hey there!

Answer = 5(x = 5)

Step-by-step explanation:

Let's solve your equation step-by-step.

5x + 3 = 6x - 2

Subtract 6x from both sides:

5x + 3 - 6x = 6x - 2 - 6x

Subtract three from both sides:

-x + 3 -3 = -2 - 2

Divide both sides by -1:


(-x)/(-1) =(-5)/(-1)

x = 5

So therefore, that is how you found your answer: x = 5

User Zaeem Sattar
by
5.9k points